Essays on the internationalization of the Turkish banking sector: the reasons and the effects on performance - Ceyhan, Şanlı Pınar. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
Sound macroeconomic policies, increasing global liquidity and higher real returns in developing countries play an important role in canalizing capital towards developing markets. High growth potential backed by an increasing population, falling inflation rates and the birth of the mortgage sector make Turkey an ideal place to expand into. This thesis aims to find the effects of globalization on the performance of the Turkish banking sector. It examines the productivity change in the sector between 1990 and 2006, with an emphasis to the period after the 2001 crisis. Using DEA, the Malmquist TFP Change Index and its mutually exclusive and exhaustive components of efficiency and technological changes are found. Additionally, technical efficiency change is further decomposed into pure technical and scale efficiency changes. The productivity of the banking sector is found out to have increased and the main reason is technological improvement. An analysis with respect to the ownership status reveals that foreign banks were the most efficient group until 2001 after which state banks captured the first place. Moreover, the analysis with respect to bank size reveals that before 2000, the most efficient bank group was the medium-scale banks followed by small banks while the efficiency scores converged after 2001. Finally, this study examines the determinants of performance by conducting a panel data fixed effects regression analysis. Efficiency change is found to be 2 negatively related to the number of branches while it is positively related to bank capitalization. Moreover, a positive relationship is found between loan ratio and performance.|Keywords; Productivity, Efficiency Measurement, Performance measurements, Data envelopment analysis, Panel data analysis
Keywords: Banks and banking -- Turkey.; Productivity accounting.; Industrial efficiency -- Measurement.; Data envelopment analysis.